2000
DOI: 10.1046/j.1365-2265.2000.01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Cranial radiotherapy of childhood brain tumours: Growth hormone deficiency and its relation to the biological effective dose of irradiation in a large population based study

Abstract: The data of this study suggest that the majority of long-term survivors of brain tumours develop GH deficiency following radiotherapy in childhood and that the adverse effects of radiotherapy may be directly related to the biologically effective dose. With longer follow-up fewer patients might respond normally to GH stimulation tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
3
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 35 publications
2
58
3
3
Order By: Relevance
“…Numerous studies found a lack in GH (GH-deficiency) to be a dose dependent adverse effect of an irradiation of the neurocranium (18,19,45,46). Surprisingly, only 1.1% of participants in our current study received a GH replacement therapy.…”
Section: Clinical Study J Gebauer E-m Fick and Others Endocrine Latecontrasting
confidence: 41%
See 1 more Smart Citation
“…Numerous studies found a lack in GH (GH-deficiency) to be a dose dependent adverse effect of an irradiation of the neurocranium (18,19,45,46). Surprisingly, only 1.1% of participants in our current study received a GH replacement therapy.…”
Section: Clinical Study J Gebauer E-m Fick and Others Endocrine Latecontrasting
confidence: 41%
“…As data from children and adolescents suggested that the highest frequency of endocrine late effects are observed in patients with Hodgkin (HL) or non-Hodgkin lymphoma (NHL) and CNS tumours (CNS-T) we restricted our analysis to these patients (15,16,17,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…There is an increase in the frequency and severity of hormonal deficits with a longer time interval after radiotherapy. The progressive nature of the hormonal deficits following radiation damage to the hypothalamic-pituitary axis can be attributed to the delayed effects of radiotherapy on the axis or the development of secondary pituitary atrophy following previous hypothalamic damage (Spoudeas et al 1996, Clayton & Shalet 1991b, Schmiegelow et al 2000. This necessitates prolonged follow-up with yearly testing of pituitary function in patients treated with cranial irradiation for brain tumours.…”
Section: Role Of Radiationmentioning
confidence: 99%
“…The formula used to calculate the BED incorporates total dose, fraction size and tissue response to radiation (Schmiegelow et al 2000). Calculation of the BED provides a useful method of comparing radiation schedules and predicting the effect on hypothalamic-pituitary function (Schmiegelow et al 2000).…”
Section: Role Of Radiationmentioning
confidence: 99%
“…GH deficiency (GHD) is an endocrinopathy found in childhood cancer survivors, resulting from tumors affecting the hypothalamic-pituitary axis or from cancer therapy, especially cranial irradiation (1,2,3). For example, GHD has been found in 58% of long-term survivors of childhood acute lymphoblastic leukemia treated with R24 Gy whole brain radiation (4).…”
Section: Introductionmentioning
confidence: 99%